Factors Associated with Uncontrolled Hypertension Among Hypertensive Patients Reported from Different Primary Health Clinics in Tuaran, Sabah, Malaysia: A Cross Sectional Study. - Rosfina GHAZALI; Khamisah Awang LUKMAN; Daw Khin Saw NAING; Fairrul KADIR; Mohammad Saffree JEFFREE; Fredie ROBINSON; Nelbon GILOI; Mohammad Yusof IBRAHIM; Urban John Arnold D'SOUZA; George George MATHEW (Turkiye Klinikleri Journal of Medical Sciences, 2020)
Objective: Hypertension is a major global issue and in an increasing trend. A disproportional balance between blood pressure controls among treated hypertensive patients is a challenge in public health as uncontrolled hypertension is the main contributor to cardiovascular, cerebrovascular and kidney diseases. Aims of the study are to determine the prevalence of uncontrolled hypertension and associated factors among hypertensive patients attending hypertension clinic at primary health clinics in Tuaran district. Justification of this study is uncontrolled hypertension causing high morbidity and mortality including premature death. Material and Methods: Study included 460 participants; is a cross-sectional study among hypertensive patient registered at three primary health clinics in Tuaran district, Sabah. Data were collected using structured modified questionnaires and analyzed using SPSS version 24.0. Results: Prevalence of uncontrolled hypertension was 45.9%. The study found that male gender (OR 2.1, 95% CI: 1.442, 3.061), high BMI status (OR 1.975, 95% CI: 1.305, 2.990), presence of diabetes mellitus (OR 3.436, 95% CI: 2.104, 5.613) and lower medication adherence (OR 1.834, 95% CI: 1.256, 2.678) were significantly associated with uncontrolled hypertension with p <0.05. Conclusion: The prevalence of uncontrolled hypertension in this study population was high with nearly half of the study population had uncontrolled hypertension. Combination of associated factors such as obesity, diabetes mellitus and lower hypertensive medication compliance had a higher impact on uncontrolled hypertension among the study group. This study further needed to address an attitudinal change, extra guidance, coaching and empowerment in the treatment of hypertension.